Get an answer in 5 minutes
We'll notify as soon as your question has been answered.
It depends on what the equation equals. But assuming ‘0’: and also if you’re meaning 2*n or n^2: 2n + 3 = 0 2n = -3 n = -3/2 Or n^2 + 3 = 0 n^2 = -3 n = sqrt(-3) n = sqrt(-1)sqrt(3) n = i sqrt(3) Where ’i’ is the imaginary number hope this answers your question.
Asked by Paige
The nth term of -1,2,7,14,23
Asked by Ramielle
Find 10th term in a rule 5n - 2
Scoodle's video lessons make learning easy and fun. Try it for yourself, the first lesson is free!